2014
DOI: 10.19173/irrodl.v15i5.1841
|View full text |Cite
|
Sign up to set email alerts
|

Democratizing higher education: Exploring MOOC use among those who cannot afford a formal education

Abstract: Massive open online courses ("MOOCs") provide free access to higher education for anyone with Internet access. MOOCs are considered a means for democratizing education. These courses will hopefully provide an opportunity for individuals to learn from the best educators in the world, as well as help expand their personal networks, and facilitate their career development. However, research thus far shows that the majority of people taking advantage of these courses are already employed, have postsecondary degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 8 publications
9
94
0
16
Order By: Relevance
“…MOOC research shows that MOOC learners are diverse in terms of cultural background and country of origin, online experience, education level, employment status and in their reasons for enrolling in a MOOC (Dillahunt, Chen & Teasley, 2014;Guo & Reinecke 2014;Woodgate, Macleod, Scott & Haywood, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…MOOC research shows that MOOC learners are diverse in terms of cultural background and country of origin, online experience, education level, employment status and in their reasons for enrolling in a MOOC (Dillahunt, Chen & Teasley, 2014;Guo & Reinecke 2014;Woodgate, Macleod, Scott & Haywood, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…MOOC learners are in their vast majority college degree holders (Despujol et al, 2014;Ding et al, 2014) and employed (Macleod, Haywood, Woodgate & Alkhatnai, 2014;Dillahunt, Wang & Teasley, 2014). Indeed, Christensen et al (2013) study reported that 83% of MOOC students have a postsecondary degree, 79.4% of students have a Bachelor's degree or higher and 44.2% indicated a level of education beyond a Bachelor degree.…”
Section: Mooc Learners' Demographicsmentioning
confidence: 99%
“…Given that one target audience of MOOCs is disadvantaged people without experience in or access to formal educational settings [6], one cannot assume that all learners have the skill set to independently direct their own learning process. Moreover, current MOOCs are frequently designed without any of these considerations; they simply deliver the content to the learner without concern for fostering effective learning strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied "MOOCs help expand their personal networks, and facilitate their career development." [12]Other reasons such as recommended by classmates to study using MOOCs, dissatisfaction with the daily classroom teaching, needing make-up study, psychological drive in being a follower accounts for the rest of 15.38%.…”
Section: Late-term Feedback Data Comparison and Analysis Mooc Efmentioning
confidence: 99%